The Relationship of Fever Onset with NS1 Examination Results, IgM, and IgG in Dengue Hemorrhagic Fever Patients - Engla Merizka; Assha Luthfianie Alifah; Sri Wahyuni Handayani; Aninda Dinar Widiantari; Farida Murtiani (Universitas Wijaya Kusuma Surabaya, 2023)
Fever onset represents the average number of days from the beginning of fever symptoms to the time when IgM and IgG examinations are conducted. Determining the right timing for these examinations can significantly impact their accuracy. In November 2021, there was a notable surge in cases of Dengue Hemorrhagic Fever at the Karawang Health Center, Sukabumi. This study aimed to investigate the relationship between the duration of fever and the results of dengue antigen and antibody tests. The research employed a descriptive analysis with a cross-sectional approach, and a sample of 50 individuals was gathered through consecutive sampling. The data was then analyzed using the Chi-Square test. The study revealed a positive correlation between the duration of fever and the outcomes of the NS1 and IgG Dengue examinations (p<0.05), highlighting the significance of timing when conducting these tests. NS1 was predominantly detected within the first three days of fever, while IgG showed reactivity after more than five days of fever. These findings underscore the importance of timing when conducting these tests and interpreting their results.